ASSESSMENT OF AIR QUALITY ACROSS DIFFERENT LAND USES IN GWAGWALADA TOWN, FCT-ABUJA, NIGERIA - Sunday, Ishaya; Omede, Emmanuel (FUDMA JOURNAL OF SCIENCES, 2022)
This study assessed ambient air quality (NO2, SO2, CO, NH3, H2S and PM10) across four different urban land uses at five points each using Handheld BW Tech GasAlert and Haze Dust Particulate Monitor in Gwagwalada town, FCT, Nigeria. The standard limit of WHO, USEPA and FME were used. CO concentration across the different land use â€œAbattoir (4.4), Market (0), Motor Park (3.4) and Roadside (6.4)â€ were within the limit of WHO, USEPA and FME (10, 9, 9 ppm/ug/m3); NO2 and H2S were within the limit of WHO, USEPA and FEME (0.07, 0.02, 0.05 ppm/ug/m3); SO2 concentration across Abattoir (0.34), Market (0.28), Motor Park (0.26) and Roadside (0.32)â€ were above the limit of WHO and FME (0.01ppm/ug/m3), but falls within the standard of USEPA (0.5ppm/ug/m3); PM10 concentration at Abattoir (142.49), Market (72.54), Motor Park (162.88) and Roadside (148.54) were within the standard of FME (250 ppm/ug/m3) and USEPA (150 ppm/ug/m3) with the exception of PM10 concentration in Motor Park  while the PM concentration were above the standard of WHO (50 ppm/ug/m3) across the different land uses. NH3 were not detected in Motor Park and Roadside, but its concentration in Abattoir (0.12) and Market area (0.1) were above the standard of WHO and USEPA (0.07) but commensurate to that of the FME.  ANOVA at 0.05% level of significance shows that there is no significant difference in the concentration of pollutants across the different land uses as justified with P â‰¤ .963. The air quality index rating depicts PM10 and
Keywords: Ambient, air, quality,Urban, pollution, USEPA, WHO, FEPA